Are We Able to Suppress Disease Activity Adequately in Patients With Established Rheumatoid Arthritis? An Observational and Cross-Sectional Study - İlker ŞENGÜL,; Seniz AKÇAY YALBUZDAĞ,; Buğra İNCE,; Altınay Göksel KARATEPE,; Taciser KAYA, (Archives of Rheumatology, 2016)
Objectives: This study aims to explore current disease activity status and simultaneous pharmacological therapies in patients with established rheumatoid arthritis (RA) to determine the extent to which treatment targets are achieved. Patients and methods: One hundred patients (7 males, 93 females; median age 57 years; range 31 to 76 years) with established RA receiving any conventional synthetic disease modifying anti-rheumatic drug (DMARD) and/or biological DMARD for at least three months were enrolled. Disease activity was determined by using the Simplified Disease Activity Index. First, patients were categorized into four groups as remission, low disease activity, moderate disease activity, and high disease activity. Then, they were divided into two subgroups, namely a remission/low disease activity subgroup and moderate disease activity/high disease activity subgroup. Results: Fifty-one percent of the patients had remission or low disease activity. The most frequently used conventional synthetic DMARDs were methotrexate (50%) and leflunomide (34%). Forty-five percent of patients were receiving glucocorticoid therapy. In patients receiving only conventional synthetic DMARDs, the proportion of remission and low disease activity was 54% (42/78). Forty-two percent (8/19) of the patients receiving biological DMARDs were in remission or had low disease activity. A comparison of subgroups revealed that median age and sulfasalazine use were significantly higher in the moderate disease activity/high disease activity subgroup. Conclusion: The results of this study demonstrated that half of patients with established RA had moderate or high disease activity in our local outpatient clinic. Some barriers might be responsible for the difficulties in controlling disease activity. Determining such barriers might result in a better clinical response during the management of patients with established RA in real-life practice.